Philosophical Hermeneutics of the Radd Concept in Article 193 KHI: A Critique of Contextual Ethics of Islamic Inheritance Law - Abdulloh Abdulloh (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The provision on Radd in Article 193 of Indonesia’s Compilation of Islamic Law (KHI), which allocates residual inheritance to all fixed heirs (dzawī al-furūḍ), including spouses, presents a paradigmatic departure from the classical Islamic legal consensus that excludes marital partners from such redistribution. This article questions whether such deviation reflects a mere juridical anomaly or a more profound philosophical reconfiguration of justice within Islamic legal thought. Adopting a conceptual framework grounded in Paul Ricoeur’s hermeneutics and John Rawls’s theory of justice, this study treats the legal text not as a static norm but as an ethically mediated narrative shaped by historical consciousness and social context. Through Ricoeur’s notion of interpretive praxis and Rawls’s difference principle, the analysis demonstrates that Article 193 embodies a transformative form of distributive justice that affirms the moral worth and relational significance of all heirs, regardless of gender or bloodline. Rather than viewing the provision as a rupture from tradition, the article argues that it constitutes a creative appropriation of Islamic inheritance principles to meet the demands of ethical pluralism and familial equity in contemporary society. The study contributes an original philosophical reading of Islamic legal reform by reimagining law as an open text, one that negotiates between normative inheritance and evolving human contexts through the lens of ethical responsibility and intersubjective recognition.